Synthesis of Acid Polyols As a Feedstock to Produce Flexible Polyurethanes and Their Effect on the Income Level of Furniture Craftsmen - Andi Budirohmi; La Ifa2; Nurjannah (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2018)
Polyuretanes are widely used as elastomers, coatings, adhesivesand binders,interior and exterior cars, furniture,shoe soles, carpets, rigit and flexible foams, membrane materials as well as constuction materials .The production of polyurethanes is largely derived from polyols derived from petroleum . Howover, petroleum is a non- renewable raw material . Thus it is necessary to look alternative feedstock for the manufacture of polyol as a polyurethane raw material. Synnthesis polyurethane by polymerization process using polyol volume based on polyol oleat acid polypropylenglycol ( PPG ) in order to know whether fatty acid can be used as raw materials of polyurethane manufacture.From the result of the study. Based on Fourier Transform Infra Red ( FTIR), showed,that the product produced is polyol with obtained hydroxyl group ( OH group )with hydroxylnumber is 129,81 mg KOH / g and 157,60 mg KOH / g sample of 70